Crisis, Recovery, and Regional Asymmetries: A Firm-Level Financial Analysis of Italian Food and Beverage SMEs - Garbelli, Maria (European Scientific Journal, ESJ, 2025)
This study investigates the financial impact of the COVID-19 pandemic on small and medium-sized enterprises (SMEs) in Italy’s food and beverage processing sector. Drawing on firm-level panel data from the AIDA database, the analysis spans the period 2019–2022 and focuses on structural resilience and heterogeneity across firm sizes and regions. A sample of 1,600 SMEs was examined, segmented by workforce size and macro-geographical area through a cluster analysis. A correlation matrix is also performed to validate results. Key performance indicators - Return on Equity, Return on Investment, debt ratio, and EBITDA per employee - were analyzed to track changes before, during, and after the crisis. Findings reveal a substantial contraction in profitability in 2020, with ROE declining by 147% in the North, while Southern firms demonstrated relatively greater resilience. ROI dropped sharply across all areas, with incomplete recovery by 2022. Debt ratios exceeded 70% sector-wide during the crisis, underscoring high financial vulnerability. EBITDA rebounded after a 10% contraction, though rising labor costs - up 8.3% by 2022 - constrained operational efficiency. Supplementary analyses include a firm-level classification of performance evolution, a correlation matrix revealing moderate alignment between investment and profitability metrics, and a cluster analysis that distinguishes between typical SME trajectories, distressed micro-firms, and structurally distinct large enterprises. The results highlight asymmetrical recovery paths shaped by firm size and regional conditions. Overall, the study underscores the importance of differentiated policy approaches tailored to the structural and territorial characteristics of the sector, to support long-term resilience and mitigate the effects of future systemic shocks.